In vitro evaluation of the marginal and internal discrepancies of different esthetic restorations (Journal of Applied Oral Science, 2013)
Objective: This study examined the fit of two types of all-ceramic single crowns and indirect composite resin full coverage crowns. Material and Methods: Thirty intact human mandibular first premolars were selected for this study and prepared using a machine to standardize the dimensions and randomly divided into 3 groups. Slip cast (IC) (In-Ceram Zirconia, Vita Zahnfabrik), copy-milled zirconia (CM) (ICE, Zirkonzahn) and indirect composite resin crowns (NECO, HeraeusKulzer, Hanau, Germany), (N=30, 10 per group) were fabricated according to each manufacturer's recommendations. Before cementation, discrepancies were measured at the marginal zone in each crown. Crowns were then cemented with G-Cem capsule self-adhesive luting cement (GC Corporation, Tokyo, Japan). Four positions were marked for each zone (mid-facial, mid-mesial, mid-distal, and mid-lingual) and three measurements were made at each of the four positions yielding to a total of 12 measurements per crown before and after cementation. The measurements were performed at a different magnification using a stereo microscope (SZ11, Olympus, Japan). Marginal, axial and occlusal zone discrepancies (µm) were evaluated after cementation. The data were statistically analyzed using two-way ANOVA and Tukey's test. Results: Before cementation, significantly less marginal discrepancies were noted compared with after cementation in all groups (p;0.05). Occlusal zone discrepancies were significantly higher than those of the marginal and axial zones in all groups (p